The effect of risk management on financial performance with good corporate governance as a moderation variable - Mardiana, Mardiana; Endah P, Puji; Dianata, Ayyu Wafiqotun Mirza (MEC-J (Management and Economics Journal), 2018)
This study aims to examine the effect of risk management proxied by the Capital Adequacy Ratio (CAR), Operating Efficiency (BOPO), and Non Performing Loan (NPL), to the financial performance projected with Return on Assets (ROA) in Islamic Banking Companies listed on the Indonesia Stock Exchange (BEI) in the period 2011 to 2016. The data used is obtained from the Financial Statements of Sharia Banking Companies Listed on Indonesia Stock Exchange in the period 2011 to 2016. After passing through the stage of purposive sampling, the worthy of used sample is 5 Companies. The results showed that the variable of Capital Adequacy Ratio (CAR), and Non Performing Loan (NPL) had negative and insignificant effect on Return on Asset (ROA), and Operating Efficiency (BOPO) had negative and significant effect on Return on Assets (ROA). Thus, the bank (issuer) is expected to pay more attention to the level of operating efficiency to improve the profitability of the company's financial performance. Meanwhile, the variable Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) did not significantly affect the Return on Asset (ROA) of the company because during the study period, the bank intermediation function was not as expected.